2020
DOI: 10.3390/ijerph17061949
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Emotional and School Adjustment in Adolescents with and without Developmental Language Disorder (DLD) Is Related to Family Involvement

Mario Valera-Pozo,
Daniel Adrover-Roig,
Josep A. Pérez-Castelló
et al.

Abstract: Developmental language disorder (DLD) refers to a language delay in the absence of other underlying causes. Individuals with DLD can also present other problems related to behavioral, scholarly, and emotional aspects of their daily lives because of their language difficulties. Moreover, these difficulties could be influenced by family and socioeconomic characteristics. Twenty-eight bilingual adolescents with and without DLD in typical schools were followed from childhood to adolescence. At age five, language a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
1
21
3
7
Order By: Relevance
“…It was predicted that there would be significant differences between parent and adolescent ratings of wellbeing, as is the case for youth with ASD (cf. Potvin et al, 2015;Egilson et al, 2017), and as has been found between tutor and adolescent ratings in DLD (Valera-Pozo et al, 2020). The findings strikingly support this hypothesis; there were significant differences across multiple well-being dimensions, for each of the three groups.…”
Section: Consistency Of Adolescent Vs Parent Reported Wellbeingsupporting
confidence: 80%
See 1 more Smart Citation
“…It was predicted that there would be significant differences between parent and adolescent ratings of wellbeing, as is the case for youth with ASD (cf. Potvin et al, 2015;Egilson et al, 2017), and as has been found between tutor and adolescent ratings in DLD (Valera-Pozo et al, 2020). The findings strikingly support this hypothesis; there were significant differences across multiple well-being dimensions, for each of the three groups.…”
Section: Consistency Of Adolescent Vs Parent Reported Wellbeingsupporting
confidence: 80%
“…This suggests that there may be poor correspondence between parent and self-report of wellbeing for children and adolescents with DLD. Indeed, there is low consistency between tutor-rated and self-rated levels of adaptability and school problems in adolescents with DLD (Valera-Pozo et al, 2020 ). However, to date no study has directly compared parent and self-report of wellbeing for children and adolescents with DLD using the same measure, making definitive conclusions difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Our data do not indicate that the mother’s education level explains any noticeable variance in early vocabulary development. Although other studies also failed to find this relation in our context [ 118 ], it is possible that this variable has a greater impact in later development.…”
Section: Discussioncontrasting
confidence: 56%
“…With respect to the mother’s education level, diverse studies have pointed out its influence in language development [ 33 , 38 , 43 ]. Nevertheless, this influence seems to be mediated by the linguistic input that the child receives [ 38 ] and the quality of parental communication (e.g., direct speech, routines…) [ 118 ]. Our data do not indicate that the mother’s education level explains any noticeable variance in early vocabulary development.…”
Section: Discussionmentioning
confidence: 99%
“…Given the exponential growth of the use of media within the family and educative settings during adolescence, the importance of both parent’s language quantity and their implication on development [ 31 , 32 , 33 ], and the presence of studies suggesting that young adults’ language level is worsening, we sought to analyze the relationship between the use of media, the quantity of parental language input, and preteens’ language development. We aimed to explore the potential relationship between media use and the linguistic level of preteens of 11 and 12 years of age.…”
Section: Introductionmentioning
confidence: 99%